Improving the competency of tahfidz Al Quran at PPTQ Ahmad Dahlan Ponorogo through the implementation of student management (BIS Humanities and Social Science, 2025)
The development of tahfidz al-Quran Islamic boarding schools is growing and even many public schools/madrasas are also implementing the tahfidz al-Quran program. On the other hand, tahfidz al-Quran is starting to be used as a jargon of excellence. but many are unsuccessful due to various factors. PPTQ Ahmad Dahlan Ponorogo is one of the tahfidz al-Quran Islamic boarding schools which is capable of producing quality graduates with good tahfidz al-Quran competencies. This research is a qualitative research with a case study approach to managing students at PPTQ Ahmad Dahlan Ponorogo in an effort to improve the competency of tahfidz al-Quran. Data collection through in-depth interviews, participant observation and documentation, researchers explored student management data at PPTQ Ahmad Dahlan Ponorogo in an effort to increase the competence of tahfidz al-Quran students and used triangulation as a data analysis method and source for this research. Through this research it can be concluded that the management of students at PPTQ Ahmad Dahlan Ponorogo goes through the process of 1) planning student input, observing and preparing the tahfidz al-Quran curriculum and 2) organizing is carried out through the division of teachers and students, 3) implementation and supervision carried out through regular monitoring and evaluation so that the management process can increase the competency of students in memorizing the Quran.